Low Molecular Weight Fucoidan Can Inhibit the Fibrosis of Diabetic Kidneys by Regulating the Kidney Lipid Metabolism. (24th November 2021) - Wang, Yan; Sun, Yanlei; Shao, Fengli; Zhang, Bo; Wang, Zhen; Li, Xinpeng
Abstract : In this study, a diabetic kidney disease model was established by placing the test rats on a high-sugar/high-fat diet combined with streptozotocin induction. Histopathological examination (H&E, Masson, and PASM stain) showed pathological changes in the diabetic rat kidneys, in addition to fibrotic symptoms and collagen deposition. Immunohistochemistry and western blot analyses indicated that the diabetic condition significantly increased the expressions of fibrotic markers including collagen, α -SMA, and fibronectin. The levels of cholesterol, triglyceride, and low-density lipoprotein were also increased in diabetic kidney disease (DKD) rat blood, while the level of high-density lipoprotein was decreased. The results of Oil red O staining experiments indicated that the kidneys of diabetic rats exhibited appreciable fat deposition, with high contents of triglyceride and cholesterol. To inhibit fibrosis and reduce fat deposition, low molecular weight fucoidan (LMWF) may be used. Based on PCR and western blot analyses, LMWF can regulate the expression levels of important lipid metabolism regulators, thereby impeding the development of kidney fibrosis. Through the vitro model, it also be indicated that LMWF could inhibit fibrosis process through regulating lipid metabolism which induced by palmitic acid.